2015
DOI: 10.1007/s00586-015-4275-5
|View full text |Cite
|
Sign up to set email alerts
|

Complication rate in adult deformity surgical treatment: safety of the posterior osteotomies

Abstract: Previous studies have shown increased complication rates with vertebral osteotomies in elderly patients, our experience support this evidence. Our study demonstrates a high incidence of intraoperative complication rate in elderly patients underwent a PSO. PSO is a demanding technique to be considered in very selected and motivated patients who must be carefully informed about the risks of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
1
19
1
1
Order By: Relevance
“…20,64 It is well recognized that older patients face greater risk for complications with ASD surgery. 22,49,55,66,67 The present study confirms this observation and provides potentially useful benchmarking data for expected complication rates based on patient age. While the rate of overall minor complications was similar across all 3 age groups assessed, the rate of major complications was progressively greater from the young to the middle-age to the elderly patient groups, suggesting that the elderly may be most vulnerable to the more serious complications.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…20,64 It is well recognized that older patients face greater risk for complications with ASD surgery. 22,49,55,66,67 The present study confirms this observation and provides potentially useful benchmarking data for expected complication rates based on patient age. While the rate of overall minor complications was similar across all 3 age groups assessed, the rate of major complications was progressively greater from the young to the middle-age to the elderly patient groups, suggesting that the elderly may be most vulnerable to the more serious complications.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies that have reported complications for ASD surgery have been limited by many factors, including retrospective design, inclusion of cases from only a single surgeon or single center, inclusion of only short-term complications, limited or poor patient follow-up, and lack of a meticulous or focused effort on recording of complications. 6,14,17,22,30,39,47,51,52,55,58 The present study was designed in an attempt to overcome these limitations, and, in doing so, has provided likely the most complete and detailed reporting of perioperative and delayed ASD surgery complications to date. The findings may prove useful for treatment planning, patient counseling, benchmarking of complication rates, and efforts to improve the safety of patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural injury is relatively low for decompression and fusion [35], but the rate may be significantly higher when osteotomies are performed [17,[36][37][38][39] (Table 1). A retrospective study of 103 ASD patients who underwent posterior arthrodesis of at least seven levels (from the thoracic spine to pelvis) reported a 17 % incidence of new neurologic deficits which persisted at the final follow-up visit [40].…”
Section: Neurologic Complications Based On Surgical Approach Posteriormentioning
confidence: 99%
“…[2][3][4] Their use is justified by the importance of sagittal correction in surgeries for deformity, but few articles describe how much of this correction is maintained because of complications that occur and the duration of follow-up in these cases. 5,6 This study surveys the mechanical complications and the evolution of sagittal spinopelvic measurements of a series of 20 patients with sagittal imbalance who underwent three-column osteotomies with follow-up for at least one year.…”
Section: Introductionmentioning
confidence: 99%